Wage Flexibility and Employment Fluctuations: Evidence from the Housing Sector - Jörn-Steffen Pischke (Institute for the Study of Labor (IZA), 2016)
Many economists suspect that downward nominal wage rigidities in ongoing labor contracts are an important source of employment fluctuations over the business cycle but there is little direct empirical evidence on this conjecture. This paper compares three occupations in the housing sector with very different wage setting institutions, real estate agents, architects, and construction workers. I study the wage and employment responses of these occupations to the housing cycle, a proxy for labor demand shocks to the industry. The employment of real estate agents, whose pay is far more flexible than the other occupations, indeed reacts less to the cycle than employment in the other occupations. However, unless labor demand elasticities are large, the estimates do not suggest that the level of wage flexibility enjoyed by real estate agents would buffer employment fluctuations in response to demand shocks by more than 10 to 20 percent compared to completely rigid wages.
Keywords: E24; J20; J44; 330; wage setting; wage rigidity; commissions; real estate agents; architects; construction workers